2016
DOI: 10.1016/j.jad.2015.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal anxiety disorder prevalence and incidence

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
176
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(201 citation statements)
references
References 51 publications
13
176
0
12
Order By: Relevance
“…This finding is similar to the reported prevalence of 10 -15% of women who have recently given birth [2]. Fairbrother N, in recent study reported prevalence ranges between 11 -21% [9]. Another study from Africa observed higher incidence as 23.4% [10].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is similar to the reported prevalence of 10 -15% of women who have recently given birth [2]. Fairbrother N, in recent study reported prevalence ranges between 11 -21% [9]. Another study from Africa observed higher incidence as 23.4% [10].…”
Section: Discussionsupporting
confidence: 89%
“…In Mexico exist different organizations focused to vigilance the violence of pregnant women, specifically in rural and indigenous zones, because the prenatal period supposes a vulnerable time lapse characterized by major susceptibility to depress, which is a pathology more disabling in a critical period of all women the witch needed self-care and care for her baby. The prevalence of depression in pregnancy and puerperal period is around 10-20%, in agree to various authors [8][9][10], however, little studies have been published related with indigenous women [11] and, few studies or none has been published for pregnant indigenous Mexican women. In regard to satisfaction surveys about life quality, although appear to be subjective methods, these can offer wellness, self-perception data and suggest a comparison point with other populations [12].…”
Section: Introductionsupporting
confidence: 78%
“…Summed scores ranged from 0-8, with higher scores denoting higher levels of anxiety. A cut-off score of two or more identified 14% of the sample as anxious, a level comparable to exisiting community data (Fairbrother et al, 2016;Grant et al, 2008).…”
Section: Antenatal Measures (Vihcs)supporting
confidence: 52%
“…The most frequent mental health problems seen antenatally are anxiety and depression -approximately one in six pregnant women have anxiety symptoms (Fairbrother et al, 2016;Grant et al, 2008) and one in ten have depressive symptoms . These symptoms affect maternal quality of life (Bauer et al, 2016;Highet et al, 2014), and have the potential to compromise maternal caregiving and maternalinfant bonding (Stewart, 2011), with developmental consequences for offspring (Goodman et al, 2011;Kingston et al, 2012).…”
Section: Introductionmentioning
confidence: 99%